Assessing the capacity of Australian broadacre mixed farmers to adapt to climate change: Identifying constraints and opportunities. (July 2016) - Brown, Peter R.; Bridle, Kerry L.; Crimp, Steven J.
Abstract: Farmers are continually striving to adapt to Australia's highly variable climate. As a function of global warming, future climatic conditions will present further challenges, but may also present many new opportunities for farmers. We involved a range of rural communities via 14 workshops across a range of Australia's large-scale broadacre cropping regions employing a rural livelihoods framework to elicit and interpret community responses. Farmers identified indicators and rated them on the extent to which they might constrain or enable adaption to increased climate variability or climate change. Financial issues, such as low equity or limited capital were considered to be most constraining, and natural capital assets, such as high soil productivity and low rainfall variability were considered to be most enabling. Most indicators were of broad-scale significance, affecting broadacre mixed farmers across a range of locations, and were not necessarily specific to climate change only. Broad-scale constraints identified were isolation/rural decline, limited access to services, poor regional infrastructure, equity/debt, and the high cost of production. Conversely, enabling factors identified were farmer education/experience, sense of community, and off-farm income. Actions to address these perceived constraints related to farm management practices, training, community, technology/research, communication, funding and institutional arrangements. In the Australian context, adapting to climate variability and change is more than just implementing a new technology, but is also about enhancing the broader resilience of the community in ways that will ensure its long term viability. To achieve this it will be necessary for different components of government and other institutional actors to work together to improve the adaptation capacity of farmers in the future. Highlights: We engaged broadacre farmers on climate adaptation using rural livelihoods. Major constraints identified were rural decline, debt and high production costs. Adaptation was enabled by experience, sense of community and off-farm income. Many indicators were broadscale and not specific to climate change. Actions were identified to enhance community resilience.